Social development of home schooled children in Metro Manila - Concepcion, Luisa Amandla U.; Dungo, Jillian Carla T.; Franco, Patricia Tanya D. (2011.)
The purpose of the study is to provide information about the home school program and social development of home schooled children in Metro Manila. It specifically aims to discover the perception of parent and the children in the home schooling program. It also intends to determine the perceptions of home schooled children on their socialization with fellow home schooled and non home schooled children, adults and other peers. Lastly, this study aims to identify the purpose of a home school support groups and the dynamics involved in it. Thirty one (31) home schooled children and twelve (12) home schooling parents from three home school support groups in Metro Manila were selected through purposive sampling. Interviews were conducted with the students. Parent respondents participated in the Focus Group Discussions separately. Observations during home school support group meeting visits were done to describe the dynamics involved in such groups. Thematic coding and analysis were used to discuss and interpret the results. Relevant sources and related theories were used to analyze the themes identified in the study. The results of the study indicated that socialization opportunities in the home schooling set-up depend on the child's exposure to different kinds of people and activities. Most of these opportunities are provided by the parents such as exposing their children to home school support groups and other extracurricular activities. Results also showed that home school support groups serve as venues for children and parents to socialize with other home schooling families through a variety of individual and group activities.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Home schooling -- Philippines; Socialization